CHALLENGES AND OPPORTUNITIES OF TALENT MANAGEMENT IN THE DIGITAL ERA ON THE PUBLIC SECTOR - Reza Reza; Rina Martina Puspitasari; Neneng Sri Rahayu; Asropi Asropi (DIA: Jurnal Administrasi Publik, 2025)
The digital era has brought significant changes to various aspects of life, including the public sector. These changes demand adaptation in human resource management, particularly in talent management. This journal conducts a literature review to examine the challenges and opportunities in talent management in the digital era within the public sector. The aim of this study is to identify the main challenges faced in recruiting, developing, and retaining talent, as well as the opportunities that can be leveraged to enhance the effectiveness of talent management in the public sector. The methodology used is a literature review by searching various leading academic databases, such as Google Scholar, to collect and analyze relevant articles. The findings show that the main challenges include changing skill requirements, competition in acquiring digital talent, and the need for adaptive development and retention strategies. On the other hand, significant opportunities arise through the utilization of digital technologies in recruitment, training, and development, as well as improved employee engagement. The conclusion of this study is that digital transformation requires the public sector to adopt a more strategic and technology-oriented approach to talent management. Recommendations for future research include in-depth exploration of the implementation of digital-based talent management strategies and evaluation of the impacts of various initiatives.